2004
DOI: 10.1080/00365540410015240
|View full text |Cite
|
Sign up to set email alerts
|

Value of Preoperative Investigations in Diagnosing Prosthetic Joint Infection: Retrospective Cohort Study and Literature Review

Abstract: The diagnosis of a prosthetic joint infection is difficult, but crucial for appropriate treatment. Scintigraphy with specific markers for infection (labelled white cells or immunoglobulin-G) has been reported as a more reliable diagnostic tool than clinical assessment (fever, fistula), laboratory studies (polynuclear neutrophil count, erythrocyte rate sedimentation, and C-reactive protein), and preoperative aspiration. In the first part of this study, we retrospectively reviewed 230 patients admitted with a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 24 publications
6
51
3
Order By: Relevance
“…While patients with connective tissue disorders were included in these studies, they were not analyzed independently from osteoarthritis. One retrospective review of 228 suspected PJIs found that CRP was more sensitive than ESR when infection was defined by a minimum of one positive intraoperative culture for virulent organisms such as streptococci species or Gram-negative bacterium or three positive intraoperative cultures for less virulent organisms like coagulase-negative staphylococci or propionibacterium species [4].…”
Section: Resultsmentioning
confidence: 99%
“…While patients with connective tissue disorders were included in these studies, they were not analyzed independently from osteoarthritis. One retrospective review of 228 suspected PJIs found that CRP was more sensitive than ESR when infection was defined by a minimum of one positive intraoperative culture for virulent organisms such as streptococci species or Gram-negative bacterium or three positive intraoperative cultures for less virulent organisms like coagulase-negative staphylococci or propionibacterium species [4].…”
Section: Resultsmentioning
confidence: 99%
“…Bernard et al (2004) retrospectively reviewed 230 patients with suspected prosthetic joint infections (hip or knee) and reviewed 33 articles dealing with preoperative evaluation of infection in prosthetic joints. They concluded that CRP and joint aspiration are the most useful tools to diagnose prosthetic joint infections, even in situations of chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…This technique carries some limitations. First, studies of preoperative joint aspiration show a wide variation in sensitivity values, ranging between 0.11 and 1.00 [6][7][8]. Low sensitivity values for fluid aspirates in chronic PJI are partly attributable to the fact that most micro-organisms in such infections grow in biofilms, attached to the implant surface (sessile bacteria).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most-used technique for reaching a bacteriological diagnosis is evaluation of fluid aspirated from the joint [6,7]. This technique carries some limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation